2020
DOI: 10.1128/iai.00859-19
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Fibronectin Binding Protein A Mediates Biofilm Development and Infection

Abstract: Implanted medical device-associated infections pose significant health risks, as they are often the result of bacterial biofilm formation. Staphylococcus aureus is a leading cause of biofilm-associated infections which persist due to mechanisms of device surface adhesion, biofilm accumulation, and reprogramming of host innate immune responses. We found that the S. aureus fibronectin binding protein A (FnBPA) is required for normal biofilm development in mammalian serum and that the SaeRS two-component system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 61 publications
(66 reference statements)
2
28
2
Order By: Relevance
“…An interesting observation throughout the time course is the overall lack of phagocytosis by monocytes, dendritic cells, and neutrophils. While this is in agreement with in vitro findings (Thurlow et al, 2011 ; Gries et al, 2020 ), a paucity of phagocytosis was observed beginning on day 3 post-infection, before the robust biofilm structure was formed. Further investigation will be required to assess the role of S. aureus biofilm molecules known to affect macrophage and neutrophil phagocytic function (Scherr et al, 2015 ; Gries et al, 2016 ; Bhattacharya et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…An interesting observation throughout the time course is the overall lack of phagocytosis by monocytes, dendritic cells, and neutrophils. While this is in agreement with in vitro findings (Thurlow et al, 2011 ; Gries et al, 2020 ), a paucity of phagocytosis was observed beginning on day 3 post-infection, before the robust biofilm structure was formed. Further investigation will be required to assess the role of S. aureus biofilm molecules known to affect macrophage and neutrophil phagocytic function (Scherr et al, 2015 ; Gries et al, 2016 ; Bhattacharya et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, this model and time frame permits the establishment of a robust infection associated with both the implant and surrounding tissue. As shown in Figures 2D,E , tissue and implant-associated bacterial burdens after 9 days were comparable to those observed in other S. aureus biofilm infection models (Yamada et al, 2018 ; Gries et al, 2020 ).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, although the roles of lipid II in the antimicrobial activity of lysocin E and nisin seem to differ, they share a common mechanism by which the antimicrobial activity modulated by ApoA-I via lipid II is enhanced, implying the existence of a series of similar antimicrobials. Other than ApoA-I, proteins in a host such as albumin are known to interact with bacteria 21,22 .…”
Section: Discussionmentioning
confidence: 99%